Copaifera duckei Oleoresin and Its Main Nonvolatile Terpenes: In Vitro Schistosomicidal Properties. Issue 10 (October 2016) - Borges, Carly H. G.; Cruz, Michele G.; Carneiro, Luiza J.; da Silva, Jonas J. M.; Bastos, Jairo K.; Tavares, Denise C.; de Oliveira, Pollyanna F.; Rodrigues, Vanderlei; Veneziani, Rodrigo C. S.; Parreira, Renato L. T.; Caramori, Giovanni F.; Nagurniak, Gláucio R.; et al.
Abstract : In this article, the in vitro schistosomicidal effects of three Brazilian Copaifera oleoresins ( C . duckei, C . langsdorffii, and C . reticulata ) are reported. From these botanical sources, the oleoresin of C . duckei (OCd) demonstrated to be the most promising, displaying LC 50 values of 75.8, 50.6, and 47.2 μg/ml at 24, 48, and 72 h of incubation, respectively, against adult worms of Schistosoma mansoni, with a selectivity index of 10.26. Therefore, the major compounds from OCd were isolated, and the diterpene, (−)‐polyalthic acid (PA), showed to be active ( LC 50 values of 41.7, 36.2, and 33.4 μg/ml, respectively, at 24, 48, and 72 h of incubation). Moreover, OCd and PA affected the production and development of eggs, and OCd modified the functionality of the tegument of S . mansoni . Possible synergistic and/or additive effects of this balsam were also verified when a mixture of the two of its main compounds (PA and ent ‐labd‐8(17)‐en‐15, 18‐dioic acid) in the specific proportion of 3:1 ( w / w ) was tested. The obtained results indicate that PA should be considered for further investigations against S . mansoni, such as, synergistic (combination with praziquantel (PZQ)) and in vivo studies. It also shows that diterpenes are an important class of natural compounds for the investigation of agents capable of fighting the parasite responsible for human schistosomiasis.